Transient extra copy of Y chromosome without driver mutation after autologous hematopoietic stem cell transplantation for acute myeloid leukemia: a case report and literature review. Issue 1 (31st December 2022) - Chen, Ying; Zou, Duobing; Niu, Tingting; Wu, Ying; Zhang, Zhaoyi; Zhang, Yi; Xu, Kaihong; Ouyang, Guifang; Mu, Qitian
Abstract : Therapy-related myeloid neoplasms (t-MNs) are associated with chemotherapy, radiotherapy, or autologous hematopoietic stem cell transplantation (auto-HSCT). Clonal abnormalities after auto-HSCT are not rare and do not always indicate t-MNs. We describe a rare case of transient clonal chromosomal abnormality after auto-HSCT for acute myeloid leukemia (AML). In this case, an extra copy of the Y chromosome accompanied by slight bone marrow dysplasia lasted for approximately 11 months and disappeared without therapy. Genetic testing of 236 hematologic malignancies showed no somatic mutations. From previously reported literature, 10 cases with the appearance of clonal chromosomal abnormalities after auto-HSCT for AML were analyzed. Six of these cases presented with persistent chromosomal abnormalities that did not develop t-MNs, one presented with inv(16) associated with therapy-related AML, and the remaining three presented with transient abnormalities. Most persistent or transient clonal chromosomal abnormalities occurring after auto-HSCT for AML could indicate a good prognosis.